2021
DOI: 10.3390/ijms22094301
|View full text |Cite
|
Sign up to set email alerts
|

The Mystery of Red Blood Cells Extracellular Vesicles in Sleep Apnea with Metabolic Dysfunction

Abstract: Sleep is very important for overall health and quality of life, while sleep disorder has been associated with several human diseases, namely cardiovascular, metabolic, cognitive, and cancer-related alterations. Obstructive sleep apnea (OSA) is the most common respiratory sleep-disordered breathing, which is caused by the recurrent collapse of the upper airway during sleep. OSA has emerged as a major public health problem and increasing evidence suggests that untreated OSA can lead to the development of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 263 publications
0
11
0
Order By: Relevance
“…High WBCs were recorded in sleep disorder patients in the present study similar finding to the results of other studies conducted earlier [ 60 , 61 ]. RBCs were in the normal range however other studies showed a higher levels of RBCs in patients with sleep disorders [ 62 ]. Haemoglobin level (7.1–17 g/dl) was different from the lower reference range however from the upper reference rage was normal.…”
Section: Discussionmentioning
confidence: 94%
“…High WBCs were recorded in sleep disorder patients in the present study similar finding to the results of other studies conducted earlier [ 60 , 61 ]. RBCs were in the normal range however other studies showed a higher levels of RBCs in patients with sleep disorders [ 62 ]. Haemoglobin level (7.1–17 g/dl) was different from the lower reference range however from the upper reference rage was normal.…”
Section: Discussionmentioning
confidence: 94%
“…Extracellular vesicles are highly enriched with proteins with different functions, such as tetraspanins (CD9, CD63, CD81, and CD82), which are involved in cell penetration, invasion, and fusion events; heat shock proteins (HSP70, HSP90), which are involved in antigen anchoring and presentation; and MVB formation proteins (Alix, TSG101), which are involved in exosomal release [ 158 ]. Additionally, cytoskeletal proteins (e.g., actin), denatured hemoglobin, proteins 4.1, 4.2, enzymes such as carbonic anhydrase, anion transport proteins (Band 3), glycoproteins (e.g., CD235a), membrane-associated proteins such as stomatin and flotillin, and CD47, which inhibits phagocytosis by interacting with macrophage signal regulatory protein alpha [ 159 ].…”
Section: Rbc-derived Extracellular Vesicles (Rbcevs): Biogenesis and ...mentioning
confidence: 99%
“…As discussed, RBCEVs possess several features that make them particularly suitable for therapeutic applications: (i) blood is easily accessible from blood banks, thus RBCs can be produced from blood at large scale and at low cost; (ii) autologous transfusion, from their own donor (or patient), or allogenic transfusion, from a universal 0-donor, of RBCEVs, are possible; (iii) RBCEVs are safer compared with other cell-derived EVs because they lack DNA, minimizing the risk of horizontal gene transfer; (iv) RBCEVs are completely nontoxic and have higher biocompatibility than synthetic EVs; (v) RBCEVs can be frozen and thawed many times without affecting their integrity and efficacy [ 158 ]. In this regard, a publication recently investigated different buffers and conditions to allow a longer stability of frozen EVs [ 195 ].…”
Section: Rbc-derived Extracellular Vesicles (Rbcevs): Biogenesis and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, intermittent hypoxia in patients with OSA provokes RMV release through ROS and iCa 2+ stresses [ 78 ]. It has been reported by in vitro studies that the detrimental effect of RMVs on eNOS activity is a causal factor for the observed endothelial dysfunction and hypertension in OSA patients [ 78 , 79 ]. In cellular microenvironments enriched in cytokines (as in the case of several inflammatory conditions), the RMVs are supposed to offer a substrate for the production of bioactive lipids (such as arachidonic acid and lysophosphatidic acid) through phosphatidylserine exposure, that have a negative impact on endothelial function and vascular integrity [ 181 ].…”
Section: Red Blood Cell Vesiculationmentioning
confidence: 99%